Peptides and Dendrimers: How to Combat Viral and Bacterial Infections - Annarita Falanga; Valentina Del Genio; Stefania Galdiero (MDPI AG, 2021)
The alarming growth of antimicrobial resistance and recent viral pandemic events have enhanced the need for novel approaches through innovative agents that are mainly able to attach to the external layers of bacteria and viruses, causing permanent damage. Antimicrobial molecules are potent broad-spectrum agents with a high potential as novel therapeutics. In this context, antimicrobial peptides, cell penetrating peptides, and antiviral peptides play a major role, and have been suggested as promising solutions. Furthermore, dendrimers are to be considered as suitable macromolecules for the development of advanced nanosystems that are able to complement the typical properties of dendrimers with those of peptides. This review focuses on the description of nanoplatforms constructed with peptides and dendrimers, and their applications.